Reconstruction of the hip joint in case of pathological dislocation of the hip in children - Alpisbaev Ch.Sh; Juraev A. M; Tapilov E. A; Kushabaev A. N (Zien Journals, 2022)
Pathological hip dislocation is one of the most severe and frequent complications of acute hematogenous osteomyelitis of the femur, suffered in the first months of a child's life and occupies a significant place in the structure of orthopedic diseases of childhood and adolescence
Keywords: osteomyelitis; hip joint; pathological dislocation of the hip; proximal end of the femur